Cyclin F‐dependent degradation of E2F7 is critical for DNA repair and G2‐phase progression - Yuan, Ruixue (EMBO J, 2019)
E2F7 and E2F8 act as tumor suppressors via transcriptional repression of genes involved in S‐phase entry and progression. Previously, we demonstrated that these atypical E2Fs are degraded by APC/C(C) (dh1) during G1 phase of the cell cycle. However, the mechanism driving the downregulation of atypical E2Fs during G2 phase is unknown. Here, we show that E2F7 is targeted for degradation by the E3 ubiquitin ligase SCF (cyclin F) during G2. Cyclin F binds via its cyclin domain to a conserved C‐terminal CY motif on E2F7. An E2F7 mutant unable to interact with SCF (cyclin F) remains stable during G2. Furthermore, SCF (cyclin F) can also interact and induce degradation of E2F8. However, this does not require the cyclin domain of SCF (cyclin F) nor the CY motifs in the C‐terminus of E2F8, implying a different regulatory mechanism than for E2F7. Importantly, depletion of cyclin F causes an atypical‐E2F‐dependent delay of the G2/M transition, accompanied by reduced expression of E2F target genes involved in DNA repair. Live cell imaging of DNA damage revealed that cyclin F‐dependent regulation of atypical E2Fs is critical for efficient DNA repair and cell cycle progression.